Therapeutic effects of vitamin D and IL-22 on methotrexate-induced mucositis in mice. Issue 1 (January 2022) - Yilmaz, Ebru; Azizoglu, Zehra Busra; Aslan, Kubra; Erdem, Serife; Haliloglu, Yesim; Suna, Pinar Alisan; Yay, Arzu Hanim; Deniz, Kemal; Tasdemir, Abdulkadir; Per, Sedat; Unal, Ekrem; Karakukcu, Musa; et al.
Abstract : Mucositis is a common side effect of cancer therapies and transplant conditioning regimens. Management of mucositis involves multiple approaches from oral hygiene, anti-inflammatory, anti-apoptotic, cytoprotective, and antioxidant agents, to cryo-therapy, physical therapy, and growth factors. There is room for novel, affordable treatment options, or improvement of currently available therapies. Vitamin D has been shown to regulate mucosa-resident cell populations such as Th17 or innate lymphoid cells and critical mucosal cytokine IL-22; however, their therapeutic potential has not been put to test in preclinical mouse models. In this study, we aimed to test the therapeutic potential of vitamin D injections and IL-22 overexpression in a murine model of chemotherapy-induced mucositis. Balb/c mice were given daily intraperitoneal injections of vitamin D. Mucositis was induced by methotrexate. Another group received IL-22 plasmid via hydrodynamic gene delivery. Weight loss and intestinal histopathology, intestinal levels of cytokines IL-22, IL-17A, GM-CSF, IL-23, IFN-γ, TNF-α, and IL-10, and number of intestinal lamina propria B cell, neutrophil, and total innate lymphoid cells were quantified. Daily vitamin D injections ameliorated intestinal inflammation and elevated intestinal IL-22 levels compared with control groups. Temporal overexpression of IL-22 by hydrodynamic gene delivery slightly increased intestinal IL-22 but failed to confer significant protection from mucositis. To our knowledge, this is the first experimental demonstration in an animal model of mucositis of therapeutic use of vitamin D and IL-22 supplementation and our results with vitamin D suggest it may have merit in further trials in human mucositis patients. Abstract : Supplemental Digital Content is available in the text.